The Digital Forensics Research Trends and Crime Scene Criminology: A Ten-Year Review (2012-2022) - Nafila, Nida; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article conducts a comprehensive decade-long review (2012-2022) of scholarly literature on "Digital Forensic" and "Crime Scene" within the field of Law. Leveraging keyword-based searches on the lens.org platform, it focuses on journal articles, revealing key insights. Universite de Lausanne emerges as the top publishing institution, while 2016 and 2019 mark peaks in publications. Computer Science dominates the field, notable authors like Claude Roux contribute significantly, and the United Kingdom stands out as the most active country. Notably, Elsevier leads in publishing, with "Digital Investigation" and "Forensic Science International" as top journals. This resource serves researchers by highlighting trends, key contributors, and prominent publishers in digital forensics and crime scene investigations over the specified timeframe.Highlights: Reveals top publishing institution and notable publication years Highlights dominance of Computer Science in the field Identifies key authors and active country in scholarly contributions Keywords: Digital Forensic, Crime Scene, Scholarly Works, Literature Review, Research Trends